Sosialisasi Pencegahan Hipertensi dan Diabetes pada Lansia Melalui Pola Makan Sehat dan Aktivitas Fisik Ringan di Desa Blangkula - Abdi, Naufal; Erwiyanti, Serly Nurfajri; Maulinasari, Maulinasari; Abdullah, Asnawi (CV. Ulil Albab Corp, 2025)
Non-Communicable Diseases (NCDs) such as hypertension and diabetes mellitus continue to pose significant health challenges, particularly among the elderly. Poor dietary habits and lack of physical activity are major risk factors often overlooked. This community service activity aimed to improve the knowledge of elderly individuals regarding the prevention of hypertension and diabetes through healthy eating patterns and light physical activity. The activity was conducted on Wednesday, July 16, 2025, in Gampong Blangkula, under the jurisdiction of Pidie Health Center. The intervention was delivered through direct verbal and interactive. Pre-tests and post-tests were administered to evaluate the changes in knowledge levels. The results showed a significant increase in the average score from 4.00 (pre-test) to 8.44 (post-test), with an average improvement of 4.44 points. These findings indicate that a simple, communicative approach can effectively enhance elderly individuals’ understanding of NCD prevention. Direct verbal education, delivered in an interactive and participatory manner, was found to be appropriate and impactful. This highlights the importance of routine, contextual nutrition education for the elderly to help them better understand, remember, and adopt healthy lifestyle practices in their daily lives.